Men and sex a sexual script approach - Graham, P. J. (Philip Jeremy) (Cambridge, United Kingdom Cambridge University Press, 2017)
"Men and Sex provides a comprehensive yet accessible account of male sexuality by using the theoretical concept of the 'sexual script' to illuminate different aspects of men's sexual behaviour. Graham begins by discussing different theories of sexuality, before providing a more detailed description of sexual script theory. This proposes how male sexual behaviour can be explained as a result of cultural influences modified by individual experience and personality as well as by interaction with others. Individual chapters detail the development of sexual scripts in childhood and adolescence, masturbation, cultural influences on sexuality, heterosexual behaviour, variations and problems in sexual functioning, homosexual behaviour, transsexualism, procreative sex, coercive sexual behaviour, the impact of physical and mental health problems on sexuality, and sexuality and pornography. The concluding chapter looks at the future of male sexuality. The book makes a valuable contribution to the burgeoning literature on masculinity studies"--Provided by publisher.
1. Introduction -- 2. The development of male sexual scripts in childhood -- 3. Self-pleasuring and sexual scripts -- 4. Male sexual scenarios -- 5. Sex with women: individual differences and interpersonal interactions -- 6. Male sexuality: variations and problems -- 7. Sex with men -- 8. Transgender and sexuality -- 9. Procreative sex: making (and not making) babies -- 10. Coercive sex -- 11. Physical and mental impairment: impact on male sexual scripts -- 12. Male sexuality and pornography -- 13. Conclusion: the future of male sexuality.
Includes bibliographical references and index.
Keywords: Sex (Psychology); Sex customs; Men -- psychology; Interpersonal relations